2020
DOI: 10.1093/jxb/eraa333
|View full text |Cite
|
Sign up to set email alerts
|

The NAC transcription factor NAC019-A1 is a negative regulator of starch synthesis in wheat developing endosperm

Abstract: Starch is a major component of wheat (Triticum aestivum L.) endosperm and is an important part of the human diet. The functions of many starch synthesis genes have been elucidated. However, little is known about their regulatory mechanisms in wheat. Here, we identified a novel NAC transcription factor, TaNAC019-A1 (TraesCS3A02G077900), that negatively regulates starch synthesis in wheat and rice (Oryza sativa L.) endosperms. TaNAC019-A1 was highly expressed in the endosperm of developing grains and encoded a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 75 publications
4
56
0
Order By: Relevance
“…ONAC127 and ONAC129 are not directly involved in starch synthesis in the rice endosperm, but they do form heterodimers that participate in apoplastic transport and the heat stress response to regulate rice grain filling, including starch accumulation ( Ren et al., 2021 ). In wheat, the endosperm-specific TaNAC019 was also found to regulate glutenin and starch accumulation by directly activating the expression of relevant genes ( Liu et al., 2020 ; Gao et al., 2021 ).…”
Section: Regulatory Network Of Starch Synthesis In Cereal Endospermsmentioning
confidence: 99%
“…ONAC127 and ONAC129 are not directly involved in starch synthesis in the rice endosperm, but they do form heterodimers that participate in apoplastic transport and the heat stress response to regulate rice grain filling, including starch accumulation ( Ren et al., 2021 ). In wheat, the endosperm-specific TaNAC019 was also found to regulate glutenin and starch accumulation by directly activating the expression of relevant genes ( Liu et al., 2020 ; Gao et al., 2021 ).…”
Section: Regulatory Network Of Starch Synthesis In Cereal Endospermsmentioning
confidence: 99%
“…A transcription factor, ZmEREB94, acts as a negative regulator of starch synthesis through regulating the expression of Shrunken-2 (sh2), Wx, SSI, BT1, and SBE1 in maize [93]. A NAC TF NAC019-A1 can bind to the promoter of the AGPase small subunit 1 and repress its expression, hence negatively regulating starch synthesis in wheat endosperms [94]. In addition, some experimental data provide evidence that some TFs regulate the accumulation of both starch and storage proteins.…”
Section: Transcriptional Regulation Network Of Starch Metabolismmentioning
confidence: 99%
“…In wheat and rice endosperms the transcription factor TaNAC019-A1 negatively regulates starch synthesis. Its overexpression reduced significantly starch content, kernel weight, and kernel width ( Liu et al, 2020 ). Recently, Song et al (2020) identified a transcriptional activator of starch synthesis (TabZIP28) in wheat.…”
Section: Starch Biosynthesismentioning
confidence: 99%